PEMBELAJARAN TEKS FABEL BERBASIS LITERASI MEMBACA UNTUK MENINGKATKAN KECERDASAN AFEKTIF PADA SISWA SMP - Ismi Izzati; Jaja Wilsa (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The purpose of this research is to explain reading literacy-based learning of fable texts to improve affective intelligence in class VII B students of SMP Negeri 11 Tegal. The research method used is qualitative with a qualitative descriptive working mechanism to describe learning fable texts. The research data is the attitude of students in carrying out literacy culture-based learning. Data collection techniques are carried out by observing, recording, and documenting techniques. Analysis of the research data is a content analysis technique. The results of this study found that learning fable texts based on reading literacy can improve the affective intelligence of class VII B students of SMP Negeri 11 Tegal. All students of class VII B have been able to determine moral values in fable texts as evidence of reading literacy activities and can then implement these moral values in everyday life.